M.N. Muravyov and Ancient Poets: Unpublished Translations - Alexander D. Ivinskiy (Studia Litterarum)
The article is devoted to the translations of M.N. Muravyov. We present more than ten unpublished texts from his Notebook, which is preserved at the Manuscripts Department of the Russian State Library: a number of works of Horace, Virgil, Anacreon, Martial, Callimachus, Lucretius and Lucan. Secondary in this context, but no less important, is the translation of a fragment from the famous poem Jerusalem Delivered by T. Tasso. These texts do not exhaust the subject (many of Muravyov’s translations still remain unpublished), but, along with others, may become the basis for the reconstruction of Muravyov’s literary position, which can already be characterized as oriented towards European “classicism.”